Predicting Free Flap Viability: Integrating Lactate and Glucose Measurements with Artificial Intelligence - Muzakkie, Mufida; Murti, Krisna; Nurmaini, Siti; Soedjana, Hardi Siswo (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Introduction: In reconstructive surgery, free flaps are a superior method for resurfacing defects. While free flap viability is typically monitored by subjective clinical examination, lactate and glucose levels in free flaps, which can affect tissue metabolism during ischaemia and reperfusion, can help predict viability. This study aims to review previous research and provide a theoretical basis for using artificial intelligence in lactate and glucose measurement as a means of assessing flap viability.Method: The primary databases used to retrieve the key medical literature presented in this study were book references and Google Scholar, PubMed and Science Direct, using search terms related to the topic. Only articles written in English and published less than ten years ago were included.Results: Lactate levels detect perfusion impairment earlier than clinical signs or other biochemical markers while glucose monitoring can indicate underlying metabolic dysregulation or physiological stress, helps early detection of complications. Combining lactate and glucose measurements enhances diagnostic accuracy and allows for timely interventions for flap viability. Studies confirm this dual monitoring is a practical, unbiased, and has the potential to be developed into an artificial intelligence tool to improve patient outcomes.Conclusion: Lactate and glucose measurements in free flap monitoring have distinct benefits. Lactate detects ischaemia and reflects tissue metabolism, while glucose monitors energy metabolism and systemic health. Combining these leading to improved flap survival rates. With accessible tools, this approach improves patient care and outcomes in reconstructive surgery.